Peran Belajar Berdasar Regulasi Diri dalam Pembelajaran Jarak Jauh (PJJ) di Masa Pandemi Covid-19 - Evi Syafrida Nasution (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
As the Coronavirus disease (COVID-19) pandemic shuts down many school buildings around the world, many schools and universities are implementing online learning. This is a new challenge in the teaching and learning process for teachers, students and parents. At the beginning of this online learning, teachers, students, and parents had to adapt quickly, where previously face-to-face learning had to switch to online learning and this is certainly not easy to do. Students are expected to be able to direct themselves in learning, so that they can follow the learning process well. The self-regulatory learning framework developed by Zimmerman (2008) has been used consistently to support students in independent learning. There are three phases of this framework, namely: planning, conducting, and evaluating. This research method is a literature study method that examines books and journals. The conclusion of this study is that learning based on self-regulation is effective in increasing student achievement in learning, with the evaluation phase students can improve or change previous strategies that are less effective so that students can show their maximum achievements